Lattice Green's Function for Multiscale Modeling of Strain Field Due to a Vacancy or Other Point Defects in Graphene. (2020) - Tewary, V.K.; Garboczi, E.J.
Abstract: A multiscale Green's function method, based upon a solution of the Dyson equation, is described for modeling the strain field due to a vacancy or any other point defect in graphene and other 2D materials. Numerical results are presented using a fourth-neighbor force-constant model for the purpose of illustration.